Autopsy case of Gaucher disease type I in a patient on enzyme replacement therapy. Comments on the dynamics of persistent storage process - Hůlková, H; Ledvinová, J; Poupetová, H; Kohout, A; Malinová, V; Elleder, M (Journal of inherited metabolic disease, 2009)
We report a female patient with Gaucher disease (GD) type I on ERT (imiglucerase) for 5 years, which led to a significant general improvement. Aged 59 years she underwent an episode of altitude sickness followed by sepsis, disseminated intravascular coagulation, and multiorgan failure. She succumbed to a cerebral haemorrhage. Autopsy revealed liver cholestatic cirrhosis and multifocal liver carcinoma with immunophenotype compatible with cholangiocarcinoma. Analysis of the storage process revealed its absence or very low levels in the majority of liver and spleen macrophages. Gaucher cells (GCs) were seen only as occasional aggregates of various sizes in these organs. GCs were seen also in the leptomeninx of the cerebellum and as infrequent perivascular clusters in both the grey and white cerebral matters. Bone marrow was heavily infiltrated with GCs, especially in the adipocyte-rich part. GCs in this location displayed varied degrees of cytoplasmic vacuolation unrelated to the lysosomal compartment, caused by droplets of triglyceride, and interpreted as due to resorption of fragments of altered white adipocytes. All these observations point to the relative efficacy of ERT in covering the standard substrate load, which should not be exceeded as it would lead to the evolution of mature GCs. The results are discussed in relation to our recently published hypothesis on GD cell pathology.
Keywords: aktivní transport; Autopsy; Female; Glucosylceramidase; glukosylceramidasa; rekombinantní proteiny; Biological Transport, Active; Gaucherova nemoc; Humans; ženské pohlaví; pitva; lidé; Middle Aged; lidé středního věku; Recombinant Proteins; Gaucher Disease